Given a polynomial P ( x ) = x 4 + a x 3 + b x 2 + c x + d ( a ; b ; c ; d are given real numbers).
Known that P(1) = 10; P(2) = 20; P(3) = 30.
Calculate 1 0 P ( 1 2 ) + P ( − 8 )
H i n t : Read the title again.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that the x -values we're interested in ( − 8 , 1 , 2 , 3 , 1 2 ) are symmetric about 2 . So define an extra polynomial Q ( x ) = P ( x + 2 ) . The information we have is: Q ( − 1 ) = 1 0 ; Q ( 0 ) = 2 0 ; Q ( 1 ) = 3 0 .
If we let Q ( x ) = x 4 + A x 3 + B x 2 + C x + D , these become 1 − A + B − C + D = 1 0 , D = 2 0 , 1 + A + B + C + D = 3 0
Substituting for D and summing the other two equations gives B = − 1 .
Now, P ( − 8 ) = Q ( − 1 0 ) and P ( 1 2 ) = Q ( 1 0 ) . In general, Q ( − x ) + Q ( x ) = 2 x 4 + 2 B x 2 + 2 D ; substituting in for x = 1 0 , B = − 1 , D = 2 0 gives Q ( − 1 0 ) + Q ( 1 0 ) = 2 0 0 0 0 − 2 0 0 + 4 0 = 1 9 8 4 0 , so the required answer is 1 9 8 4 .
Problem Loading...
Note Loading...
Set Loading...
We can use Bezout's polynomial remainder theorem by defining an extra polynomial Q(x) = P(x) - 10x (1).
We know 1;2;3 are solutions for Q(x). Hence Q(x) = (x-1)(x-2)(x-3)(x-m) (m is another solution for Q(x), since Q(x) is a fourth degree polynomial).
Substituting Q(x) in (1) gives us P(x)= (x-1)(x-2)(x-3)(x-m) + 10x.
Now we can easily calculate 1 0 P ( 1 2 ) + P ( − 8 ) (While calculating, you may notice m is eliminated). The answer is 1 9 8 4